Dinamika Pendekatan Maʿnā cum Maghzā dalam Konteks Akademik Indonesia - Fitriatus Shalihah (Nun: Jurnal Studi Alquran dan Tafsir di Nusantara, 2022)
An approach certainly does not exist in a vacuum but is inseparable from the study and construction of the thoughts of its predecessors. This is also the case with the maʿnā-cum-maghzā approach, a new method of understanding texts initiated by Sahiron Syamsuddin. This article discusses the dynamics of the maʿnā-cum-maghzā approach in the history of Indonesian scholarship. The questions to be answered in this study are how did the maʿnā-cum-maghzā approach emerge in Indonesia? What is the portrait and dynamics of the maʿnā-cum-maghzā approach in Indonesia? How do Indonesian academics respond to the presence of maʿnā-cum-maghzā? With an accentuation on the bibliographic research model, it is found that maʿnā-cum-maghzā is the result of a form of continuity and change to previous studies, especially in the works of Nasr Hamid Abu Zayd, Abdullah Saeed, and Fazlur Rahman. Methodically, maʿnā-cum-maghzā is similar to Fazlur Rahman's double movement and Abdullah Saeed's contextualization. However, after maʿnā-cum-maghzā was introduced as a method, especially from 2009 until this research was written (September 2021) there have been hundreds of Indonesian academics who are interested in studying and applying it to texts, both religious and non-religious texts. This phenomenon shows that the study of maʿnā-cum-maghzā in Indonesia is dynamic, especially in relation to its implications for the Qurʾān and hadith.